Volodymyr Olexandrovіch Radchenko - «SISJP NAMS», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
The article deals with the life and scientific way of well-known traumatologist-orthopaedist, a talented surgeon, Deputy Director for Science, Head of the Department of instrumental and minimally invasive spine surgery of SI "Sytenko Institute of Spine and Joint Pathology NAMS of Ukraine", Doctor of Medical Sciences, professor Radchenko Vladimir Alexandrovich, who celebrated his 60th anniversary March 24, 2016.